Subtotal petrosectomy in cochlear implantation: Subtotalna petrozektomija pri kohlearni implantaciji - Rebol, Janez (Acta Medico-Biotechnica, 2024)
The main indication for subtotal petrosectomy (SP) in cochlear implant surgery is chronic otitis media with or without cholesteatoma. In addition to chronic otitis, other indications for surgery include inner ear malformations with the possibility of cerebrospinal fluid leakage and anatomical abnormalities. The main goal of the surgical technique is to eliminate the inflammation in the mastoid cavity and insert an electrode into the inner ear. Over the past thirteen years, the procedure has been performed in 15 patients with an average follow-up of 61 months. In all patients, complete insertion of the electrode was achieved, and the cavity was filled with abdominal fat.Revision surgery was required in three patients with preservation of the device. All patients are still using the cochlear implant.Subtotal petrosectomy is a safe procedure. However, follow-up is required for at least ten years after surgery. Meticulous surgery with removal of all disease, middle ear mucosa, and epithelium, the complete sealing of the external ear canal, and covering of the implant to prevent extrusion are critical for a successful surgical result.
Keywords: subtotal petrosectomy, cochlear implantation, chronic otitis, deafness, inner ear malformations